Insulin-like growth factor 2 mRNA-binding protein 2: a potential link between type 2 diabetes mellitus and cancer - Cao, Junguo; Yan, Weijia; Ma, Xiujian; Huang, Haiyan; Yan, Hong (The journal of clinical endocrinology & metabolism, 2021)
Type 2 diabetes mellitus (T2DM) and cancer share a variety of risk factors and pathophysiological features. It is becoming increasingly accepted that the 2 diseases are related, and that T2DM increases the risk of certain malignancies.This review summarizes recent advancements in the elucidation of functions of insulin-like growth factor 2 (IGF-2) messenger RNA (mRNA)-binding protein 2 (IGF2BP2) in T2DM and cancer.A PubMed review of the literature was conducted, and search terms included IGF2BP2, IMP2, or p62 in combination with cancer or T2DM. Additional sources were identified through manual searches of reference lists. The increased risk of multiple malignancies and cancer-associated mortality in patients with T2DM is believed to be driven by insulin resistance, hyperinsulinemia, hyperglycemia, chronic inflammation, and dysregulation of adipokines and sex hormones. Furthermore, IGF-2 is oncogenic, and its loss-of-function splice variant is protective against T2DM, which highlights the pivotal role of this growth factor in the pathogenesis of these 2 diseases. IGF-2 mRNA-binding proteins, particularly IGF2BP2, are also involved in T2DM and cancer, and single-nucleotide variations (formerly single-nucleotide polymorphisms) of IGF2BP2 are associated with both diseases. Deletion of the IGF2BP2 gene in mice improves their glucose tolerance and insulin sensitivity, and mice with transgenic p62, a splice variant of IGF2BP2, are prone to diet-induced fatty liver disease and hepatocellular carcinoma, suggesting the biological significance of IGF2BP2 in T2DM and cancer.Accumulating evidence has revealed that IGF2BP2 mediates the pathogenesis of T2DM and cancer by regulating glucose metabolism, insulin sensitivity, and tumorigenesis. This review provides insight into the potential involvement of this RNA binding protein in the link between T2DM and cancer.